Synthesis and antiproliferative action of a novel series of maprotiline analogues - MEEGAN, MARY; MCCABE, THOMAS (My University, 2014)
The synthesis of a diverse library of compounds structurally related to maprotiline, a norepinephrine reuptake transporter (NET) selective antidepressant which has recently been identified as a novel in vitro antiproliferative agent against Burkitt?s lymphoma (BL) cell lines is reported. A series of 9,10-dihydro-9,10-ethanoanthracenes was synthesised with modifications to the bridge of the dihydroethanoanthracene structure and with alterations to the basic side chain. A number of compounds were found to reduce cell viability to a greater extent than maprotiline in BL cell lines. In addition a related series of novel 9- substituted anthracene compounds was investigated as intermediates in the synthesis of 9,10-dihydro-9,10-ethanoanthracenes. These compounds proved the most active from the screen and were found to exert a potent caspase-dependant apoptotic effect in the BL cell lines, while having minimal effect on the viability of peripheral blood mononuclear Cells (PBMCs). Compounds also displayed activity in multi-drug resistant (MDR) cells.
PUBLISHED
Keywords: Burkitt?s lymphoma